Metastatic esophageal cancer presenting as shock by injury of vagus nerve mimicking baroreceptor reflex: A case report. Issue 49 (December 2017) - Tsuchihashi, Kenji; Yoshihiro, Tomoyasu; Aikawa, Tomomi; Nio, Kenta; Takayoshi, Kotoe; Yokoyama, Taku; Fukata, Mitsuhiro; Arita, Shuji; Ariyama, Hiroshi; Shimizu, Yukiko; Yoshida, Yuichiro; Torisu, Takehiro; et al.
Abstract: Rationale: Neurogenic shock is generally typified by spinal injury due to bone metastases in cancer patients, but continuous disturbance of the vagus nerve controlling the aortic arch baroreceptor can cause shock by a reflex response through the medulla oblongata. Patient concerns: A 43-year-old woman with dysphagia presented to our hospital. Computed tomography showed a primary tumor adjacent to and surrounding half the circumference of the descending aorta, and multiple cervical lymph node metastases, including a 55 × 35-mm lymph node overlapping the root of the left vagus nerve. Squamous esophageal cancer (T4bN3M1, stage IV) was diagnosed. Whereas shock status initially appeared soon after left cervical pain, suggesting pain-induced neutrally-mediated syncope, sustained bradycardia and hypotension occurred even after alleviation of pain by opioids. Diagnosis: Disturbance of the left vagus nerve associated with the aortic arch baroreceptor by a large left cervical lymph node metastasis was considered as the cause of shock, pathologically mimicking the baroreceptor reflex. Interventions: Systemic steroid administration was performed, and radiotherapy for both the primary site and lymph node metastasis was started 2 days after initiating steroid treatment. Outcomes: Four days after initiating steroid administration, hypotension and bradycardia were improved and stable. Lessons: Disturbance of the vagus nerve controlling the aortic arch baroreceptor should be kept in mind as a potential cause of neurogenic shock in cancer patients, through a pathological reflex mimicking the baroreceptor reflex.